Considerations in the design of randomized trials to screen for type 2 diabetes. (June 2014) - Echouffo-Tcheugui, Justin B; Prorok, Philip C
Background: Randomized controlled trials (RCTs) are the most robust and valid approach to evaluate screening for diseases. Many in the diabetes research community have advocated sole reliance on RCTs for designing diabetes screening policies. However, the challenges of conducting RCTs of screening for type 2 diabetes may have been underappreciated. Purpose: Discuss the key theoretical concepts and practical challenges of designing and conducting RCTs of diabetes screening. Methods: Narrative and critical review of the literature pertaining to the theory and practice of designing and conducting RCTs of diabetes screening. Results: We present the theoretical basis of a diabetes screening trial, using concepts developed mainly in studies of cancer screening and illustrations from the Cambridge component of the Anglo Danish Dutch Study of Intensive Treatment In peOple with screeN-detected diabetes in primary care (ADDITION-Cambridge), the only extant trial of diabetes screening. We examine design issues, including the appropriate trial question, choice of design, and duration of follow-up, and address aspects of trial implementation, including recruitment, randomization, endpoint determination, sample size requirements, and screening interval. Limitations: The limited number of trials of diabetes screening did not permit us to illustrate many of the practical difficulties one encounters when implementing theoretical concepts. Conclusion: When diabetes screening trials are planned, we suggest careful consideration to potential areas of practical difficulty, especially the need for particularly large sample sizes and extended follow-up, and the choice of appropriate outcomes and screening intervals.